KEGIATAN MEMBUAT MOZAIK DENGAN MEDIA KAPAS UNTUK MENGEMBANGKAN KETRAMPILAN MOTORIK HALUS ANAK - Indrayani, Sri; Hermahayu, Hermahayu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2013)
This research aims to know the influence of the activities of Making Mosaics fine motor Skills Against Cotton in children. This research is a research experiment with the model One Group Pre Posttest Design by performing the measurement of initialand final measurement. the subject of this research is the son of a kindergarten Chrysanthemum IX Nampurejo Purwodadi Purworejo as much as 3 students. Sampling techniques using Total Sampling. This research using the method of data collection in the form of sheets of Observation. Data analysis techniques used are analysis techniques Test rank signed Wilcoxon with the help of the program SPSS For Windows Version 17.00. The results showed that the activity of making mosaics cotton effect on fine motor skills in children. The initial value of the fine motor skills of at least 26 children and up to 31. Then after being given the treatment makes the final measurement value cotton mosaic of at least 57, 62 maximum value. Tested with the help of SPSS Test Rank Signed Wilcoxon. Statistical tests showed Asymp. SIG (2-Tailed) = 0.00102 α = 0.005 < then formulated a hypothesis, that the activity of making mosaics cotton was able to develop fine motor skills, accepted and proven true.